Increase in dimethylsulfide (DMS) emissions due to eutrophication of coastal waters offsets their reduction due to ocean acidification - Gypens, Nathalie; Borges, Alberto V. (Frontiers in Marine Science, 2014)
Available information from manipulative experiments suggested that the emission of dimethylsulfide (DMS) would decrease in response to the accumulation of anthropogenic CO2 in the ocean (ocean acidification). However, in coastal environments, the carbonate chemistry of surface waters was also strongly modified by eutrophication and related changes in biological activity (increased primary production and change in phytoplankton dominance) during the last 50 years. Here, we tested the hypothesis that DMS emissions in marine coastal environments also strongly responded to eutrophication in addition to ocean acidification at decadal timescales. We used the R-MIRO-BIOGAS model in the eutrophied Southern Bight of the North Sea characterized by intense blooms of Phaeocystis that are high producers of dimethylsulfoniopropionate (DMSP), the precursor of DMS. We showed that, for the period from 1951 to 2007, eutrophication actually led to an increase of DMS emissions much stronger than the response of DMS emissions to ocean acidification.